Wistful thinking: Making Inuit labour and the Nanisivik mine near Ikpiarjuk (Arctic Bay), northern Baffin Island - Tester, Frank; Lambert, Drummond; Lim, Tee (Études/Inuit/Studies, 2013)
AbstractThis article interrogates discourse about Inuit in relation to employment issues and the Inuit response to “what was good for them” at the intersection of colonial and postcolonial thought in the 1970s. Attempts to integrate Inuit with a modern industrial economy occurred after Inuit had moved, or been moved, from land-based hunting and trapping camps to new settlements developing in the eastern Arctic. We examine the planning stage (1970-1976) of the Nanisivik mine at Strathcona Sound on the northern tip of Baffin Island that operated from 1976 until 2002. Building on the work of James O’Connor in the early 1970s and concepts of legitimisation and accumulation functions of the State, and using the archival records of the Department of Indian Affairs and Northern Development and the Department of Energy, Mines, and Resources, we explore the extent to which Inuit were constructed as “labour in need of employment.” In examining debate between officials of these departments, we seek to find out to what extent other needs went unmet, based on experience with the Rankin Inlet Nickel Mine (1957-1962). Inuit resistance to this definition and the relationship between Inuit as hunters and Inuit as wage earners are explored with reference to contemporary mining development in Nunavut.